2018
DOI: 10.1002/2017jd027965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Satellite‐Based Evapotranspiration Models of the Nagqu River Basin of the Tibetan Plateau

Abstract: Evapotranspiration (ET) is one of the major uncertain components of the energy and water cycle and was derived for the Nagqu River Basin based on remote sensing data and atmospheric surface layer observations under cloudless conditions. Two process‐based models were used to determine the ET: a Priestley‐Taylor (PT)‐based model and a topographical enhanced surface energy balance system (TESEBS) model. Improved broadband albedo, downward shortwave radiation flux, and reconstructed normalized difference vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 81 publications
(91 reference statements)
2
10
0
Order By: Relevance
“…Based on the original 10‐day MVC synthetic product, a new time series of a cloud‐free data set was constructed by applying the HANTS algorithm. In the HANTS algorithm, cloud removal is combined with a smoothing process using a Fourier analysis, and those pixels identified as cloudy are replaced by a filtered value (Zou et al, ). Details on the HANTS algorithm can be found in Verhoef ().…”
Section: Methodsmentioning
confidence: 99%
“…Based on the original 10‐day MVC synthetic product, a new time series of a cloud‐free data set was constructed by applying the HANTS algorithm. In the HANTS algorithm, cloud removal is combined with a smoothing process using a Fourier analysis, and those pixels identified as cloudy are replaced by a filtered value (Zou et al, ). Details on the HANTS algorithm can be found in Verhoef ().…”
Section: Methodsmentioning
confidence: 99%
“…The forcing data were produced by merging a variety of data sources, including data from the China Meteorological Administration station, TRMM satellite, GEWEX Surface Radiation Budget (GEWEX‐SRB), and the Global Land Data Assimilation System (Ma et al, ). Additionally, some in situ measurements and independent data sets have been used to evaluate the forcing data (Chen et al, ; Zou, Zhong, Ma, Hu, Huang, et al, ). In this study, the CMFD radiation product was also selected an existing product for intercomparison.…”
Section: Datamentioning
confidence: 99%
“…The transformed NDVI or transformed squared NDVI might also overestimate or underestimate the fractional vegetation cover [41]. However, a recent study by Zou et al [42] found that the land surface heat fluxes were less sensitive to NDVI than the temperature-related variables and wind speed (~0.4% changes in land surface temperature would cause~11% changes in ET, while~10% changes in NDVI would only causẽ 0.2% changes in ET). Nevertheless, it is really a good suggestion for us to implement spectral mixture analysis methods in our future work to improve the accuracy of surface heat flux estimation.…”
Section: Discussionmentioning
confidence: 99%
“…The ECOSTRESS (ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station) is designed to accurately measure the land surface temperature and evaporative stress index, which may substantially improve our understanding of energy and water transfer in the atmospheric boundary layer. Since the land surface temperature is one of the most important parameters in surface heat flux estimation and the evapotranspiration was estimated to be the most sensitive to land surface temperature [42], the potentially higher accuracy of land surface temperature measurement may further reduce the errors in energy flux retrievals. The Sentinel-3 is aimed at measurements of land surface temperature, sea surface temperature, sea surface topography, and sea surface color with high accuracy, which may be very useful for the comprehensive study of land-atmosphere and sea-atmosphere interactions.…”
Section: Discussionmentioning
confidence: 99%